2013
DOI: 10.1016/j.hlc.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Validation of EuroSCORE II in Chinese Patients Undergoing Heart Valve Surgery

Abstract: The EuroSCORE II model gives an accurate prediction for individual operative risk in patients undergoing single valve surgery but an imprecise prediction in patients undergoing multiple valve surgery at our centre. Therefore, the use of the EuroSCORE II model for risk evaluation may be suitable in patients undergoing single valve surgery, and the creation of a new model which accurately predicts outcomes in patients undergoing multiple valve surgery is possibly required at our centre in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 13 publications
3
24
0
4
Order By: Relevance
“…(23) In another study comparing the EuroSCORE II in a Turkish cohort of 428 patients, the model was shown to underestimate mortality risk for the entire cohort. (24) Our study cohort, though small, showed a similar pattern with the predicted mortality being underestimated in the entire cohort but overestimated in the lower risk AVR and MV repair groups.…”
Section: Infective Endocarditismentioning
confidence: 99%
“…(23) In another study comparing the EuroSCORE II in a Turkish cohort of 428 patients, the model was shown to underestimate mortality risk for the entire cohort. (24) Our study cohort, though small, showed a similar pattern with the predicted mortality being underestimated in the entire cohort but overestimated in the lower risk AVR and MV repair groups.…”
Section: Infective Endocarditismentioning
confidence: 99%
“…en algunos de los artículos se hace distinción entre la cirugía con y sin circulación extracorpórea 259 ; en otros se distinguen las cirugías valvulares dependiendo de cual sea la válvula intervenida 202,257,272 ; y, en artículos basados en el análisis de predictores de estancias prolongadas en UCIs y complicaciones postoperatorias se ha preferido describir todos los tipos de cirugías sin intentar agrupar en grupos más generales 232,260 .…”
Section: Discussionunclassified
“…En los artículos publicados en España sobre este tema, En cuanto al SAPS III, son pocos las publicaciones en las que vemos la utilización de esta escala en la población sometida a cirugía cardiaca, ya que como hemos podido comprobar los resultados obtenidos no corresponden con los observados en la realidad, no es una escala diseñada específicamente para cirugía cardiaca y la discriminación observado es pobre. 272 . También se ha observado mejor poder de discriminación cuando la etiología de la patología valvular es no reumática en comparación con la patología valvular de origen reumático 270 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Similar differences combined with altered risk-adjusted mortality were also found in China and India when compared with that of STS and EuroSCORE II sample population undergoing valve surgeries. [101415] It is recommended that each population validates its own cardiac surgical patient subject. EuroSCORE, after all, is not meant to be universal, but just a guide.…”
Section: Nonmodifiable Factorsmentioning
confidence: 99%